Le silence de la mer [videorecording (DVD)] = The silence of the sea - Melville, Jean-Pierre, 1917-1973; Melville, Jean-Pierre, 1917-1973; Vernon, Howard, 1914-1996; Stéphane, Nicole, 1928-2007; Robain, Jean-Marie (Actor); Vercors, 1902-1991 (Criterion collection, 2015)
1941. An idealistic, naive German officer in Nazi occupied France is assigned to the home of a middle-aged man and his grown niece. Their response to his presence - their only form of resistance - is complete silence.